Blue horizon - Smith, Wilbur A (London Zaffre, 2018)
A Courtney series adventure - Book 3 in the Birds of Prey trilogy Jim sprang back on to the truck of the violently rocking wagon, and stared across at Manatasee. She saw him and pointed her assegai at his face. Then he saw the length of slow-match had been exposed across the last yard of trampled earth below the mound on which the queen stood. The swift flame shot along it, leaving the fuse blackened and twisted as
1
Keywords: FICTION -- Action & Adventure; Courtney family (Fictitious characters) -- Fiction